Modification of both functional neurological symptoms and neuroimaging patterns with a good anatomoclinical concordance: a case report - Galli, Silvio; Aybek, Selma; Chokron, Sylvie; Moulin, Thierry; Magnin, Eloi (BMC neurology, 2019)
Background In the nineteenth century, Jean Martin Charcot explained functional neurological disorder (formerly called conversion disorder) as a “psychodynamic” lesion. Numerous advances in neuroimaging have permitted identification of the neural underpinnings of this disorder. Case presentation Herein we describe a case of functional neurological disorder (FND) with initial left sensorimotor deficit, in-coordinated limb movements, neglect, clouded consciousness, slurred speech and a semiology of visual impairment. A single photon emission computed tomography (SPECT) showed a right thalamic hypoperfusion, which is rather concordant with the initial semiology. Later, the semiology changed, presenting with a predominantly neurovisual complex presentation. The second SPECT showed no more thalamic abnormalities but an hypoperfusion in the right temporo-occipital junction, right inferior parietal lobe and left superior frontal lobe, which is also rather concordant with the changing semiology. Conclusions This case illustrates the evolving neuroimaging patterns of FND but also the concordance between semiology and neuroimaging findings in FND supporting Charcot's theory of “dynamic lesion”.